TINGKAT PENGETAHUAN LANSIA TERHADAP OSTEOARTHRITIS KNEE DI POSYANDU ANGGREK TUNJUNG SEKAR - Fajrin, Muhammad Andhika Noval; Rosidah, Nikmatur; Sucahyo, Eleonora Elsa (Jurnal Pengabdian Pada Masyarakat METHABDI, 2023)
Osteoarthritis of the knee is a degenerative joint disease characterized by pathological symptoms in the entire joint structure, cartilage damage, development of osteophytes and sclerosis at the edges of the bones, stretching of the joint capsule, inflammation and weakness. the muscles around the joint. Risk factors for knee osteoarthritis are genetics, age, gender, obesity and metabolic disorders. This study aims to determine the level of knowledge of elderly people regarding knee osteoarthritis. This type of research uses outreach and poster methods as output results. Before being given counseling, 0% of the 10 respondents did not know information related to knee osteoarthritis, but after being given the counseling, 100% of the 10 respondents were able to answer all questions in the questionnaire correctly. There is a difference in respondents' knowledge before and after being given education about knee osteoarthritis.